Social dialogue and the recession - Demetriades, Stavroula; Kullander, Mats (Dublin, 2009)
"This paper aims to give a flavour of the latest developments across Europe and inform policy makers of topical issues. It will present measures taken in response to the recession (both employment market measures and financial stimulus packages), outline the extent of social partner involvement, and the actions taken so far by the social partners. According to the European Commission, there is still room for policy learning across Member States (European Commission, 2009c p. 42). The material for this report has been gathered mainly from Eurofound’s European Industrial Relations Observatory (EIRO) and from its European restructuring monitor (ERM), and is supplemented by findings from desk research."